Feasibility study of a loss-driven earthquake early warning and rapid response systems for tunnels of the Italian high-speed railway network. Issue 112 (September 2018) - Fabozzi, S.; Bilotta, E.; Picozzi, M.; Zollo, A.
Abstract: Linear infrastructures have strategic importance and impact on the social and economic conditions of many countries, hence the seismic risk management of existing and new designed ones is a crucial issue in earthquake-prone areas. High-speed and high capacity railways are an example of infrastructures that assume increasing importance in developed countries, since they permit rapid transit of people and freight. Due to the seismicity of the country, the case of the high-speed railways Italian network appears suitable for assessing the feasibility of a loss-driven earthquake early-warning system based on the real-time estimation of the expected damage probability and lead-time. Among the several subsystems that compose the network, the paper focuses on tunnels, since they are largely present along the route of the existing high-speed lines and of the new ones currently under design. This work describes a procedure that exploits the disaggregation of the seismic hazard to define sets of virtual seismic sources potentially affecting railway's tunnels. Hence, the probability of seismic damage to tunnel structures and the time available for implementing real-time mitigation procedures can be calculated. Such a procedure is applied to two tunnels of the high-speed system with different structural layout. The procedure suggests that for the considered tunnels the best option for undertaking seismic risk mitigation measures would be an on-site threshold–based early-warning system. However, the foreseen probability of structural damage to the tunnel lining is low in both cases. The proposed methodology can be easily generalized to different targets to design the optimal configuration of an earthquake early warning system, and applied to control, manage and maintain the tunnel structures along the high-speed railway network. Highlights: Seismic vulnerability assessment of underground tunnels using fragility curves. Feasibility of a loss earthquake early warning systems based on the real-time estimation of the expected damage probability and lead-time. The disaggregation of the seismic hazard is exploited to define the virtual seismic sources. Hence the probability of seismic damage and the available time for implementing in real-time seismic risk mitigation procedures is proposed. The procedure shows a potential for the possible implementation of Earthquake Early Warning Systems on existing tunnels and can be used for later and more advanced stages of the design of new tunnels.